2017
DOI: 10.1007/s11517-017-1673-3
|View full text |Cite
|
Sign up to set email alerts
|

Using nonlinear finite element models to analyse stress distribution during subluxation and torque required for dislocation of newly developed total hip structure after prosthetic impingement

Abstract: Dislocation is a serious potential complication of total hip replacement. Previous studies have proposed a newly developed total hip structure that meets the required oscillation angle of 120°, for which the chamfer on the acetabular liner rim was designed to enable the neck to impinge on the chamfer over a large area after impingement occurs. This study adopted the finite element method to further analyse the torque limits leading to dislocation and the contact stresses at the impingement and egress sites of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…The minimum forces are likely to be valuable target values for designing a new type of artificial hip joint. Moreover, impingement of the femoral neck on the acetabular cup is induced by an inadequate range of hip joint movement [13,17,53]. We will conduct further analyses to study the effects of pull-out direction or loading torque on the pull-out behavior of the joints.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The minimum forces are likely to be valuable target values for designing a new type of artificial hip joint. Moreover, impingement of the femoral neck on the acetabular cup is induced by an inadequate range of hip joint movement [13,17,53]. We will conduct further analyses to study the effects of pull-out direction or loading torque on the pull-out behavior of the joints.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that the femoral heads and acetabular cups with a relatively large diameter increased the range of motion after THA and decreased the risk of dislocation. Using finite element analysis, Chi et al [17] also verified that an increased size of the heads and cups resulted in a significant increase in the torque value, which induced dislocation after prosthetic impingement occurred. Human artificial hip joints with structures for preventing dislocation have been previously developed and utilized clinically.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of its excellent conductive and favorable bioactive properties, it is widely preferred as a biomaterial of choice in both dentistry and orthopedics [29,30]. While one of the advantages of carbon fiber is that it is biocompatible [31][32][33][34], promotes bone growth on the surface, and has mechanical characteristics similar to cortical bone, there is a reduction in stress shielding. Under the same constraint and load conditions shown in Figure 4a, the results on the von Mises stress distribution for the rod topologically optimized in composite material are reported in Figure 11.…”
Section: Reduction In Stress Shielding With Carbon Fiber Prosthesesmentioning
confidence: 99%
“…A patient who undergoes hip dislocations has reduced mobility, which directly affects the quality of life and increases the costs to the health system (Brown and Callaghan, 2008). Management of THA instability remains a surgical challenge and represents a multifactorial problem that includes the patient condition, surgical technique, implant component design and orientation, bone quality, and surrounding soft tissues (Brown and Callaghan, 2008;Barrack, 2003 Gao et al, 2018;Chi et al, 2018). All previous studies showed an added value with respect to a rigid body dynamics analysis.…”
Section: Introductionmentioning
confidence: 99%